2016
DOI: 10.1016/j.jand.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

He Said, She Said: Examining Parental Concordance on Home Environment Factors and Adolescent Health Behaviors and Weight Status

Abstract: Introduction Few studies have examined concordance/discordance between caregivers to identify whether caregivers see familial and parental factors in the home environment similarly or differently and whether the agreement or disagreement is related to adolescent obesity risk. Answers to these questions are important and may inform whether family-based childhood obesity interventions need to target both parents. Objective The main objective of the study is to examine whether and how parental concordance/disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
0
24
1
Order By: Relevance
“…13 Further, adolescent females with reports of higher family functioning had lower BMI z-scores and rates of overweight/obesity, less sedentary behaviour, and consumed more fruits and vegetables. 17,18 Adolescent males with higher family functioning had greater physical activity and less sedentary behaviour, but not lower BMI z-scores or weight status. 17,18 Families with impaired family functioning may have challenges with every day communication, providing rules, structure, and support.…”
Section: Family Functioning and Youth Obesitymentioning
confidence: 93%
See 2 more Smart Citations
“…13 Further, adolescent females with reports of higher family functioning had lower BMI z-scores and rates of overweight/obesity, less sedentary behaviour, and consumed more fruits and vegetables. 17,18 Adolescent males with higher family functioning had greater physical activity and less sedentary behaviour, but not lower BMI z-scores or weight status. 17,18 Families with impaired family functioning may have challenges with every day communication, providing rules, structure, and support.…”
Section: Family Functioning and Youth Obesitymentioning
confidence: 93%
“…17,18 Adolescent males with higher family functioning had greater physical activity and less sedentary behaviour, but not lower BMI z-scores or weight status. 17,18 Families with impaired family functioning may have challenges with every day communication, providing rules, structure, and support. 7,14 These challenges can further extend to making healthy specialty clinics for more intensive family-based behavioural treatment with a multidisciplinary treatment team.…”
Section: Family Functioning and Youth Obesitymentioning
confidence: 93%
See 1 more Smart Citation
“…Parenting partnership or ‘co‐parenting’ is the term used to describe the relationship that both parents share in raising children . The quality of the parenting partnership has been shown to positively impact a child's social and emotional development, including impulse control, which suggests that it might influence a child's lifestyle behaviour and weight status.…”
Section: Introductionmentioning
confidence: 99%
“…8 Parenting partnership or 'co-parenting' is the term used to describe the relationship that both parents share in raising children. 9 The quality of the parenting partnership has been shown to positively impact a child's social and emotional development, including impulse control, [10][11][12] which suggests that it might influence a child's lifestyle behaviour and weight status. However, a systematic review of 213 studies on childhood obesity interventions found no interventions that focused on the parenting partnership in relation to dietary intake or childhood obesity.…”
Section: Introductionmentioning
confidence: 99%